Investigation and comparison of three noval strain rate-dependent fracture criteria. Issue 11 (24th July 2021) - Huang, Yahui; Tuo, Zhiyu; Qu, Keyu; Yue, Zhenming; Badreddine, Houssem; Gao, Jun; Qiu, Yuliang; Sun, Jiao
Abstract : In this study, three new strain rate-dependent fracture criteria were proposed and studied upon DP900 steel. The damage threshold was rewritten as a function related to strain rate on the basis of Lou's fracture theory. Three different uncoupled strain rate base forms were also given: (i) two polynomial forms and (ii) one power form. The model parameters were identified and validated through uniaxial tensile and double bridge shear tests. The prediction accuracies of each model within four different strain rates were compared by contrasting and analysing the experimental and numerical results. In conclusion, the proposed fracture criteria of power form induce the results with the best agreements with experimental ones. These results prove that the proposed fracture criteria can predict ductile failure under different strain rate loadings.